India food security portal - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
The India Food Security Portal presents current information about agriculture, food security, and nutrition in India and about dynamic developments in the region’s food system. It is facilitated by the International Food Policy Research Institute (IFPRI) and brings together a network of regional partners.